Supplier Selection Analysis Using Minmax Multi Choice Goal Programming Model - Dewi, Novi Rustiana; Susanti, Eka; Suprihatin, Bambang; Cahyono, Endro Setyo; Permata, Anggun; Yanita, Nurul Fadhila (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
Production control, inventory and distribution is an important factor in trading activities. These three factors are discussed in a system called Supply Chain Management (SCM). Procurement of goods from a company or trading business related to suppliers. In some cases, there are several supplier that can be assessed by considering certain factors. In certain cases, the data from several factors that are considered are uncertainty, so the fuzzy approach can be used. The MINMAX Multi Choice Goal Programming model can be used to solve fuzzy supplier selection problems with linear membership function. It can be applied to selecting supplier of Brastagi Oranges. There are four suppliers, namely Jaya, Mako, Baros.Â Gina. There are three factor to consider, cost, quality and delivery. The decision maker select the best supplier for ordering 17000 kg Brastagi oranges. The results, the best supplier is Gina with an order quantity of 10000 kg and Mako with a total order of 7000 kg